Pediatric Shunt Revision Analysis Within the First Year of Shunt Placement : A Single Center Experience - Muhammad Azzam, - (2021)
Abstract Background: Hydrocephalus is a common problem in neurosurgery with shunt placement remains the mainstay of the management. However, shunt placement generally requires following surgical procedures, including shunt revision. Despite the recent developments, the incidence of shunt failure remains high, approximately 30-51% in the 1st year following the shunt placement.